DOES TECHNOLOGY PROFICIENCY INFLUENCE STUDENT ATTITUDES IN ACCOUNTING CLASSES ENHANCED BY AUGMENTED REALITY? - Abanum , Collins Ifeanyichukwu; Alabi, B O; Akinpelu, M O A; Akintula , Oluwashina Elijah; Aina, Jeremiah Oluwafemi (Top Educational Review Journal (TERJ), 2025)
This study investigates the influence of technology proficiency on student attitudes in augmented reality-enhanced accounting classes in Nigerian secondary schools. ARS has emerged as an innovative instructional tool for teaching complex financial concepts, such as partnership and goodwill accounts. However, disparities in digital literacy among students, often driven by socioeconomic factors, raise questions about its inclusivity and effectiveness. Students were categorized into high, average, and low technology proficiency levels using a quasi-experimental design and taught using ARS. Attitude outcomes were measured using the Accounting Student Attitude Questionnaire, while pretest scores were controlled using ANCOVA. The results revealed no statistically significant difference in attitude scores across proficiency levels (F (2, 37) = 0.550, p = .581, Partial Eta Squared = .029), indicating that ARS fosters positive emotional engagement regardless of students’ prior technological skills. The findings underscore the potential of ARS as an inclusive and user-friendly instructional strategy capable of bridging gaps in digital readiness and promoting equitable learning experiences. This study highlights the importance of integrating ARS into educational practices, particularly in resource-constrained environments, to enhance motivation and accessibility for diverse learners